2014
DOI: 10.1007/s00381-014-2596-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of complex multiloculated hydrocephalus in infants and children

Abstract: Both open and endoscopic fenestration appeared effective at improving shunt management. The endoscopic technique may offer advantages in operative time, blood loss, and length of hospital stay. These data suggest that endoscopic fenestration may be used as the initial approach for treatment of multiloculated hydrocephalus, with craniotomy and open fenestration used for more severe or refractory cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…However, there were some limitations to that study including the fact that there were several surgeons, it was a retrospective analysis and there was bias associated with procedure selection according to disease severity. Furthermore, predetermined specific clinical and radiological criteria were not considered when selecting surgical options1).…”
Section: Endoscopy For Fenestration Of Mlhmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were some limitations to that study including the fact that there were several surgeons, it was a retrospective analysis and there was bias associated with procedure selection according to disease severity. Furthermore, predetermined specific clinical and radiological criteria were not considered when selecting surgical options1).…”
Section: Endoscopy For Fenestration Of Mlhmentioning
confidence: 99%
“…Uniloculated hydrocephalus is defined as cystic dilatation of one part of the normal ventricular system such as obstruction of one of the foramina of Monroe or an isolated fourth ventricle obstruction3). MLH is also referred to as multilocular hydrocephalus, multiseptate hydrocephalus, polycystic hydrocephalus, ventricular compartmentalization, intraventricular septations and multicompartmental hydrocephalus1,26).…”
Section: Introductionmentioning
confidence: 99%
“…This retrospective cohort study concluded that endoscopic fenestration may represent the preferred initial treatment for many of these cases, primarily due to lower surgical morbidity, and suggested that open fenestration may be best reserved for more severe cases or those that have failed prior endoscopic surgery [1].…”
mentioning
confidence: 97%
“…Dear Editor, We read with great interest the recent article BSurgical management of complex multiloculated hydrocephalus in infants and children^by Akbari et al [1], concerning the open and endoscopic fenestration of complex cysts in multiloculated hydrocephalus.…”
mentioning
confidence: 99%
“…With improvements in endoscopic technique, a similar result can be achieved in a less invasive way. A comparison of open craniotomy versus endoscopy in the adjuvant management of multiloculated hydrocephalus demonstrated an average of 5.1 subsequent shunt-related interventions in the craniotomy group versus 3.1 in the endoscopy group ( p = 0.25) [82] . Although this did not achieve statistical significance, endoscopy was associated with decreased blood loss, and shorter operative time and hospital LOS.…”
Section: The Adjuvant Role Of Endoscopy In Shuntingmentioning
confidence: 99%